Analisis Potensi Pajak Restoran dan Kontribusinya pada Pendapatan Asli Daerah Kabupaten Badung - Made Wulandewi, Desak; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2020)
The purpose of this study is to determine the potential and contribution of restaurant tax in Kuta district as a source of PAD in Badung Regency. This research was conducted in 73 restaurants, 11 restaurants and 4 bars in Kuta District with the method of determining the probability sampling method, namely simple random sampling. Data collection is done by non-participant observation and questionnaires. The analysis technique used is quantitative descriptive. Based on the results of the study, it is known that the potential for restaurant tax in Kuta District is in a very stable (optimistic) condition of 77,787,570,060 rupiahs. In a stable (moderate) economic condition the target was set at 29,429,630,673 rupiahs and in an economic condition that was less stable (pessimistic) at 25,929,190,020 rupiahs. The contribution of restaurant taxes in Kuta district from the number of samples that researchers used in this study amounted to 0.55 percent of the revenue of Badung Regency PAD. Keywords: Potential; Contribution; Local Original Revenue.